Novel method for spectrophotometric analysis of hydrochlorothiazide tablets using niacinamide as hydrotropic solubilizing agent - Maheshwari, R K; Shukla, Ravi Shankar (Asian Journal of Pharmaceutics (AJP), 2014)
In the present investigation, 2 M niacinamide (an inexpensive drug) solution was employed as hydrotropic solubilizing agent to solubilize poorly water-soluble drug hydrochlorothiazide for its spectrophotometric analysis. The proposed method is new, simple, environmentally friendly, accurate, and reproducible. Accuracy, reproducibility, and precision of the proposed method were validated statistically.